Understanding the Impact of Social Media on Mental Health in Autistic Youth and Expanding Access to Culturally Responsive Behavioral Health Services in Underserved Communities - Ayowole Samuel Ajiboye; Tahir Kolawole Balogun; Paul Okugo Imoh; Amina Catherine Ijiga; Toyosi Motilola Olola; Emmanuel Oluwasayomi Ahmadu (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Autistic youth face an elevated risk of mental health disorders, with emerging evidence linking excessive social media use to heightened psychological distress. This review investigates how digital engagement intersects with systemic inequities to impact the mental health of autistic adolescents in underserved communities. Drawing on a convergent mixed-methods design, the study integrates psychometric data, digital behavior metrics, and stakeholder narratives to examine the nuanced effects of platform-specific social media usage, cultural stigma, and behavioral health access disparities. Findings reveal that increased engagement with algorithm-driven platforms like TikTok and Instagram correlates with higher anxiety and depression scores, particularly in youth from low socioeconomic and racially/ethnically marginalized backgrounds. Concurrently, structural barriers—including cultural incongruence, geographic isolation, and limited provider diversity—significantly reduce access to autism-informed behavioral health services. Gender-diverse and non-binary autistic individuals report the highest psychological distress, further emphasizing the need for intersectional frameworks. The analysis also shows that culturally inclusive interventions, digital literacy programs, and community awareness campaigns markedly improve service utilization and reduce therapy dropout rates. These results underscore the critical need for adaptive, neurodiversity-affirming mental health strategies that integrate digital risk management and culturally responsive care. The study advocates for co-designed interventions leveraging telehealth, ethical AI tools, and community-based literacy initiatives to promote psychological resilience in autistic youth navigating digital ecosystems and systemic marginalization.